2021
DOI: 10.3390/su13179969
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Earnings Management: Moderating Impact of Economic Cycles and Financial Performance

Abstract: This study analyses the relationship between earnings management and corporate social responsibility. To this end, we use a sample of 568 listed companies from the European Union between 2010 and 2018. We use discretionary accruals as the measure of earnings management, under the Modified Jones model. Corporate social responsibility is proxied by the Combined Environmental, Social and Governance Score from the ASSET4 database. We find a negative relation between earnings management and corporate social respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 46 publications
4
38
1
2
Order By: Relevance
“…In short, the effect of CSR practices is not uniform because not all of the stakeholders of companies consider the sustainability criterion in their decisions, which, therefore, Huang and Watson (2015) contradicts this trend of thinking that the relationship between social and environmental practices and company performance is always positive because, for them, although there is considerable evidence on the relationship between CSR and financial performance, the results are mixed-making it difficult to draw a definitive conclusion. In the same approach, Gonçalves et al (2021a) and Margolis et al (2009) argue that the relationship of CSR practices varies over time, suffering the effect of the innovation of technologies. Servaes and Tamayo (2013) reinforce this approach by proclaiming that the impacts of CSR on company performances depend on the level of customer or stakeholder awareness regarding CSR.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the effect of CSR practices is not uniform because not all of the stakeholders of companies consider the sustainability criterion in their decisions, which, therefore, Huang and Watson (2015) contradicts this trend of thinking that the relationship between social and environmental practices and company performance is always positive because, for them, although there is considerable evidence on the relationship between CSR and financial performance, the results are mixed-making it difficult to draw a definitive conclusion. In the same approach, Gonçalves et al (2021a) and Margolis et al (2009) argue that the relationship of CSR practices varies over time, suffering the effect of the innovation of technologies. Servaes and Tamayo (2013) reinforce this approach by proclaiming that the impacts of CSR on company performances depend on the level of customer or stakeholder awareness regarding CSR.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Proof of this are the numerous academic researches and initiatives promoted by business entities, NGOs, and bodies linked to the UN (Barbieri and Cajazeira 2012). However, scientific studies regarding the benefits of CSR and their impact on the performance of the company have contradictory results (Elliott et al 2014;Gonçalves et al 2021a;Hahn and Kühnen 2013;Hong et al 2012;Huang and Watson 2015). Karabolad (2008) states that since its origin, the socio-environmental movement is not configured as an integrated and homogeneous movement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim et al [40] found that CSR firms have lower levels of discretionary accruals, and Cho et al [41] showed that CSR performance decreases information asymmetry. Moreover, Goncalves, Gaio, and Ferro [42] found that more socially responsible companies have higher quality financial reporting. We use MSCI ESG KLD's measures of environmental, social, and governance practices, which they express as strengths and concerns, and a net score of the strengths minus the concerns scores.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…In turn, greater trust helps establish an enabling environment for companies to grow and invest in innovation. This whole framework has led to several studies on the relationship between CSR and financial performance, but, despite the remarkable strategic benefits for the entity, results are still inconclusive (Orlitzky et al 2003;Blomgren 2011;Ducassy 2013;Michelon et al 2013;Atmeh et al 2020;Boukattaya and Omri 2021;Gonçalves et al 2021a).…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%